A compendium of current developments on polysaccharide and protein-based microneedles - Fonseca, Daniela F. S. (2019)
Microneedles (MNs), i.e. minimally invasive three-dimensional microstructures that penetrate the stratum corneum inducing relatively little or no pain, have been studied as appealing therapeutic vehicles for transdermal drug delivery. Over the last years, the fabrication of MNs using biopolymers, such as polysaccharides and proteins, has sparked the imagination of scientists due to their recognized biocompatibility, biodegradability, ease of fabrication and sustainable character. Owing to their wide range of functional groups, polysaccharides and proteins enable the design and preparation of materials with tunable properties and functionalities. Therefore, these biopolymer-based MNs take a revolutionary step offering great potential not only in drug administration, but also in sensing and response to physiological stimuli. In this review, a critical and comprehensive overview of the polysaccharides and proteins employed in the design and engineering of MNs will be given. The strategies adopted for their preparation, their advantages and disadvantages will be also detailed. In addition, the potential and challenges of using these matrices to deliver drugs, vaccines and other molecules will be discussed. Finally, this appraisal ends with a perspective on the possibilities and challenges in research and development of polysaccharide and protein MNs, envisioning the future advances and clinical translation of these platforms as the next generation of drug delivery systems.